Directory of Science Communication Courses and Programs in the United States. - Reese, Stephen D.; Carothers, Diane (Journalism Quarterly)
Reviews the book `Directory of Science Communication Courses and Programs in the United States,' compiled by Sharon Dunwoody and Jocelyn Steinke.